Effects of the Japanese Encephalitis Virus Genotype V-Derived Sub-Viral Particles on the Immunogenicity of the Vaccine Characterized by a Novel Virus-Like Particle-Based Assay - Sarah Honjo; Michiaki Masuda; Tomohiro Ishikawa (Vaccines, 2019)
Japanese encephalitis virus (JEV) is classified into five genotypes labelled I through V. Although the genotype V (GV) JEV was originally found and had apparently been limited in Malaysia for more than 50 years, its emergence in Korea and China has recently been reported. Therefore, the GV JEV might be spreading over new geographical regions as a cause of potential public health problems. However, it is unknown whether the currently available JEV vaccines are effective against the emerging GV strains. To investigate this issue, a novel virus-like particle-based neutralizing assay was developed in this study. By using this assay, the inactivated JEV vaccine used in Japan and the recombinant sub-viral particles (SVPs) bearing the E protein of the GV Muar strain were characterized for the immunogenicity against the GV JEV. Although the inactivated vaccine alone failed to elicit a detectable level of neutralizing antibodies against the GV JEV, the vaccine added with the Muar-derived SVPs induced relatively high titers of neutralizing antibodies, associated with the efficient Th1 immune responses, against the GV JEV. The results indicate that addition of the GV JEV-derived antigens may be useful for developing the vaccine that is universally effective against JEV including the emerging GV strains.